Analisis Kesesuaian Materi IPA dengan Tujuan Kurikulum pada Buku Teks Pelajaran IPA SMP/MTs Kelas VII Semester 1 untuk Diintegrasikan dengan Materi Kebakaran - Dessi Verawati; Ahmad Fauzi; Ramli Ramli (Universitas Negeri Padang, 2018)
Indonesia is the country that is prone to disaster. One of the disasters that are happening in Indonesia is fire. Many fire disasters occur and cause damage that is not a little. Therefore, the necessary efforts to reduce the risk of catastrophic fires. Fire hazard mitigation efforts can be done by providing knowledge and understanding through education in schools. Granting of knowledge and understanding of the catastrophic fires done by integrating disaster material into subjects. The subjects can be integrated material fires one of these subjects is IPA. In fact, in the implementation of learning at the school there has been no integrated material fire. Before integrating the material fire, needs to be done analysis of the suitability of the curriculum aim at a textbook lesson in IPA and IPA material compliance with the material fire. This research aims to know the suitability of the curriculum aim at a textbook lesson in IPA SMP/MTs Class VII semester 1 of aspects of conformance with SKL, KI, KD, scientific approach and assessment of authentic. Then the suitability of material fires with material sience on a textbook lesson IPA SMP/MTs Class VII semester 1 of the suitability of the realm of knowledge, i.e. factual knowledge, conceptual and procedural.Type of this research is descriptive research with qualitative approach. The subject is a textbook lesson IPA SMP/MTs Class VII semester 1 published by A, B and C. Sampling technique used was purposisve sampling. Data collection instruments consist of sheets of the conformity analysis of the goals of the curriculum on a textbook lesson IPA SMP/MTs Class VII semester 1 and sheet material suitability analysis of fires with material science.Results of the study the suitability of a textbook lesson in IPA/MTs Class VII semester 1 with curriculum to books published by A 84.61% kesesuian percentage obtained (very appropriate), B 84.13% (very appropriate) and a textbook lesson published by C was 46, 93% (less fit). As for the suitability of the material with fire IPA SMP/MTs Class VII semester 1 obtained percentage on KD 3.1 20% category is not appropriate; KD 3.2 20% category is not appropriate; KD 3.3 40% category is less appropriate; KD 3.4 40% category are less aopropriate and KD 3.5 46.67% category is quite appropriate.